Effect of Genistein-rich Edamame Extract on Eosinophil-Lymphocyte Ratio - Pratama, Reza Dian; Basyar, Edwin; Sudjarwo, Aries (RSUP Dr. Kariadi, 2024)
BACKGROUND : Atherosclerosis is associated with hypercholesterolemia and inflammation. Edamame, a high-genistein soybean variant, is believed to have protective effects against atherosclerosis. AIMS : This study aimed to determine the influence of edamame extract rich in genistein on the eosinophil-lymphocyte ratio (ELR) levels in rats induced with atherosclerosis. METHOD : This research utilized a true experimental design with a post-test only control group. Thirty male rats were divided into five groups: negative control, positive control, treatment 1 with edamame extract supplementation, treatment 2 with edamame extract rich in genistein supplementation, and treatment 3 receiving atorvastatin. After 28 days, the ELR levels were examined from rat blood. Data were analyzed using One-Way ANOVA - Bonferroni, Kruskal-Wallis – Mann-Whitney, and Pearson correlation tests. RESULT : There were no significant differences in ELR levels (p>0.05) among all treatment groups compared to the negative and positive control groups. T-tests between the negative control and positive control groups, as well as between the positive control and the three treatment groups successively, showed non-significant results (p: 0.376; 0.856; 0.169; 0.066). CONCLUSION : The administration of edamame extract rich in genistein did not significantly reduce inflammation levels in blood vessels compared to edamame extract alone, as indicated by non-significant results in the ELR difference analysis.